Factors Influencing Parents in Choosing SD IT Cahaya Bangsa in Semarang City with Trust as a Moderating Variable - Achmad Afif Fikri; Joko Sutarto; Kardoyo Kardoyo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Choosing an elementary school is a complex decision for parents, influenced by multiple factors. This study aims to analyze the determinants of parents’ decisions in selecting an Integrated Islamic Elementary School (SDIT), identify the most dominant factor, and examine the moderating role of trust. The research was conducted at SDIT Cahaya Bangsa, Semarang City, using a quantitative approach with multiple regression and Moderated Regression Analysis (MRA). Data were collected through a closed-ended questionnaire from 244 parents and analyzed using SPSS software. The findings indicate that religious values (B = 0.363), school services (B = 0.259), character education (B = 0.186), and school quality (B = 0.167) significantly influence parents’ decisions. Conversely, potential development (B = 0.017; p = 0.814) shows no significant effect. Trust significantly moderates the influence of potential development (B = 0.017; p = 0.013) but weakens the effect of school services (B = -0.022; p = 0.000). Religious values emerge as the most dominant factor. This research contributes theoretically by incorporating trust into the educational decision-making model, addressing a gap in studies on Integrated Islamic Schools. The results provide practical insights for schools to enhance their strategies and build stronger relationships with parents in supporting student development.